PENGARUH KUALITAS KERJA, PARTISIPASI, KESEMPATAN BERKEMBANG DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KARYAWAN PT. KEMILAU INDAH PERMANA DI KARANGANYAR - F.X. Ichtiardi, Suprayitno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
ABSTRACT The objective of this research is to reveal positive influence and quality significance, participation, developing chance and communication the same time. In addition, it reveals as well the relation between an individual and productivity in PT Kemilau Indah Permana in Karanganyar. The result of multiple linier regression analysis shown as the quality of variable regression coefficient (X1), participation (X2) and developing chance (X3) give positive influences to productivity. Whereas communication variables (X2) has negative influence to productivity. The result of research t shows that quality variable (X1) gives positive and significant influence to productivity, participation variable and developing change variable (X3) have it as well, but communication variable (X2) shows a negative and insignificant influence to quality productivity. Meanwhile, the result of research F reveals that quality variable (X1), participation (X2), developing chance (X3), and communication (X4) at the same time give a significant influence to productivity variable of the employees in PT Kemilau Indah Permana Karanganyar. Analysis of determination coefficient (R2)(X3) and communication (X4) give a 96,3% influence to productivity. Keywords: Quality, participation, developing chance, communication productivity